2011
DOI: 10.1183/09031936.00056111
|View full text |Cite
|
Sign up to set email alerts
|

Physiological changes during low- and high-intensity noninvasive ventilation

Abstract: In a physiological randomised cross-over study performed in stable hypercapnic chronic obstructive disease patients, we assessed the short-term effects of two settings of noninvasive ventilation.One setting was aimed at maximally reducing arterial carbon dioxide tension (Pa,CO 2 ) (highintensity ( We conclude that while Hi-NPPV is more effective than Li-NPPV in improving gas exchange and in reducing inspiratory effort, it induces a marked reduction in CO, which needs to be considered when Hi-NPPV is applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
2
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 28 publications
4
73
2
7
Order By: Relevance
“…However, it may be speculative whether the extent of airflow obstruction in this group would solely explain the diminished HRQOL or whether the effects of NIV by resting the respiratory muscles and reducing the work of breathing during NIV application may lead to an enhanced HRQOL. 23 Respiratory muscle function impairment is known to occur not only in subjects with COPD with hypercapnic respiratory failure but also in subjects with COPD in early disease stages, 24,25 and NIV application may therefore account for HRQOL benefits. It is of interest that the NIV group still presented with elevated P aCO 2 levels when compared with the LTOT group despite highintensity NIV, aiming to reduce P aCO 2 to normal values.…”
Section: Hrqolmentioning
confidence: 99%
“…However, it may be speculative whether the extent of airflow obstruction in this group would solely explain the diminished HRQOL or whether the effects of NIV by resting the respiratory muscles and reducing the work of breathing during NIV application may lead to an enhanced HRQOL. 23 Respiratory muscle function impairment is known to occur not only in subjects with COPD with hypercapnic respiratory failure but also in subjects with COPD in early disease stages, 24,25 and NIV application may therefore account for HRQOL benefits. It is of interest that the NIV group still presented with elevated P aCO 2 levels when compared with the LTOT group despite highintensity NIV, aiming to reduce P aCO 2 to normal values.…”
Section: Hrqolmentioning
confidence: 99%
“…Another very recent physiological randomised crossover study confirmed that high-intensity NPPV is more effective than conventional (low-intensity) NPPV in improving gas exchange and in reducing inspiratory effort [33]. However, this study also revealed that high-intensity NPPV may induce a reduction in cardiac output.…”
Section: Conventional (Low-) Versus High-intensity Nppv: Rctsmentioning
confidence: 54%
“…Several trials have now established this concept for COPD patients [11,17,[24][25][26][27][28][29][30][31][32][33]. For the purpose of maximally decreasing elevated Pa,CO 2 values, controlled ventilation with high IPAP levels typically ranging 20-40 cmH 2 O is implemented in the hospital setting and subsequently used for HMV.…”
Section: High-intensity Nppv Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the studies performed in CRF we have learnt that higher inspiratory pressures are necessary to improve gas exchange. However, we are insufficiently informed about probable disadvantages of this high-intensity NIV [Lukácsovits et al 2012]. In the study of Struik and colleagues the highest pressures were used indeed leading to improved gas exchange while clear benefits in terms of survival or readmission rates did not result [Struik et al 2014b].…”
Section: Introductionmentioning
confidence: 99%